A study on dengue fever presentation and outcome in Hospital Universiti Sains Malaysia - Ismail, Abdullah Lutfi (2020)
Dengue fever is one of the most endemic infectious disease in Malaysia and the number of cases increases each year. Patients may present in various phases and forms of dengue, which can progress to severe dengue. The aims of this study were to determine the presentations of dengue infection and factors associated with severe complications. Methods: This retrospective study involved patients aged 12 years and above with positive dengue infection presented to emergency department in our tertiary, suburban hospital and admitted, from year 2016-2018. Patients sociodemographic patterns, presentation and complications of dengue were identified. Factors associated with severe dengue were determined. Results: A total of 327 cases were included, with 66 patients (20.2%) contracted severe dengue. Most common symptoms was loss of appetite (75.2%), followed by fever (65.7%) and vomiting (55.7%). Most common complication was dengue shock syndrome (18.3%) followed by respiratory distress (1.2%). Factors predictive of severe dengue include shortness of breath (AOR 5.82, 95% CI 1.37-24.69, p=0.017), diarrhoea (AOR 0.49, 95% CI 0.27-0.91, p=0.023), tachycardia (AOR 2.85,95% CI 1.59-5.10, p=0.001 and hepatomegaly (AOR 2.76, 95% CI 1.24-6.18, p=0.013). Conclusions: Identifying factors predictive of severe dengue may help physicians in prioritizing the patients care and anticipate deterioration and complications. Factors associated with severe dengue in this study were shortness of breath, diarrhea, tachycardia and hepatomegaly.